Pengaruh Desain Henna, Persepsi Harga dan Word of Mouth Terhadap Minat Beli Konsumen - Nia Nuraeni; Rita Tri Yusnita; Suci Putri Lestari (Univiversitas Dr. Djar Wattiheluw, 2022)
This study aims to determine and analyze the effect of henna design, price perception and word of mouth on consumer buying interest in Ve Henna Art Tasikmalaya henna wedding painting services. The method used in this research is descriptive quantitative method with a consumer survey approach with a sample of 80 respondents. The data collected in the form of primary data through a questionnaire. Analysis of the data in this study using multiple regression analysis, correlation coefficient and coefficient of determination using the SPSS application. The results showed that the henna design price perception and word of mouth simultaneously had a significant effect on consumer buying interest. Henna design and partial price perception has a significant effect on consumer buying interest, but word of mouth partially has no significant effect on consumer buying interest.